2017
DOI: 10.1038/eye.2016.310
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a new hydrophilic acrylic supplementary IOL for sulcus fixation in pseudophakic cadaver eyes

Abstract: Purpose Management of refractive errors after cataract surgery includes spectacles or contact lens, secondary laser vision correction, intraocular lens (IOL) exchange, or piggyback lens implantation. We evaluated for the first time a single-piece hydrophilic acrylic IOL designed for supplementary sulcus fixation in postmortem pseudophakic human eyes. Methods Pseudophakic human cadaver eyes were imaged by anterior segment optical coherence tomography (AS-OCT) to assess position of the primary IOL. Eyes were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 24 publications
0
24
2
Order By: Relevance
“…No complications were observed during surgery or in the postoperative period, which is a finding similar to previous studies involving the same ciliary sulcus lens family. 10,11,14,15,24 The design of the tested lenses supports the integrity and physiologic function of the anterior segment of the eye. Intraocular pressure remained practically unchanged in these studies.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…No complications were observed during surgery or in the postoperative period, which is a finding similar to previous studies involving the same ciliary sulcus lens family. 10,11,14,15,24 The design of the tested lenses supports the integrity and physiologic function of the anterior segment of the eye. Intraocular pressure remained practically unchanged in these studies.…”
Section: Discussionmentioning
confidence: 84%
“…7,9 Unlike historical approaches, when inserting the secondary IOL into the capsular bag (piggybacking) used to be the general practice in the implantation of supplementary IOLs, the most advanced additional lenses are specifically designed for implantation into the ciliary sulcus, meaning sufficient space remains between the two lenses, and the development of interlenticular opacification is minimal. 10 Furthermore, manufacturers are making great efforts to design lenses that efficiently eliminate all complications that may arise from polypseudophakia or from the ciliary sulcus being the implantation site, such as iris chafing, pigment dispersion syndrome, pupillary block, angle-closure and secondary glaucoma. 7,[10][11][12][13] The aim of this study was to present the initial results obtained in connection with the implantation of the 1stQ AddOn ® diffractive supplementary IOL produced by Medicontur Medical Engineering Ltd (Zsámbék, Hungary) in pseudophakic patients who had previously had various monofocal capsular bag IOLs implanted.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only peer-reviewed study discussing this new secondary IOL (that we are aware of) was a study performed on postmortem pseudophakic human eyes 14. The results of the study suggested that the distance between the primary in-the-bag lens and the AddOn secondary lens was sufficient and predictable.…”
Section: Introductionmentioning
confidence: 99%